PENERAPAN METODE HANDLUNGSORIENTIERUNG DALAM PEMBELAJARAN BAHASA JERMAN PADA SMA DI KOTA SORONG - Limahelu, Florence I. L. R.; Karuna, Kalvin; Marantika, Juliaans E. R. (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2024)
This study aims to describe the implementation of the Handlungsorientierung approach in German language teaching at the senior high school level. The research employed a qualitative descriptive method using questionnaires distributed to German language teachers in various high schools. The findings indicate that although most teachers are not academically familiar with the theory of Handlungsorientierung, they have implemented its principles through learning activities such as role-playing, product creation (videos, emails, posters), and other collaborative tasks. Teachers consider this approach effective, enjoyable, and capable of increasing student engagement. However, its implementation is challenged by limited instructional time and insufficient facilities. Based on these findings, it is recommended that teacher training be enhanced and supporting infrastructure be improved to enable the more optimal application of this approach.